Kajian Yuridis Masyarakat Hukum Adat - Wihelmus Jemarut; Solikatun Solikatun; Pahrur Rizal (Widya Yuridika, 2022)
The Indonesian Parliaments has included a law draft concerning about customary law community in the National Legislation Program Priority of 2020 – 2024, while the provisions on customary law communities have been regulated in several laws.  The questions that is examined in this article are  how are the regulations regarding customary law communities in the laws and regulations and what is the evaluation of these laws and regulations? This study uses a a statutory approach.  The results show that the provisions regarding customary law community are sporadically regulated in Law no. 5 of 1960, Law no. 39 of 1999, Law no. 41 of 1999, Law no. 7 of 2004, Law no. 18 of 2004, Law no. 27 of 2007, and Law no. 2 of 2009. Several evaluation points are (1) the recognition of customary law communities whose conditionality causes the recognition of customary law communities only at the level of discourse; (2) the use of the term is inconsistent; (3) the implementing regulations of Article 18 B paragraph (2) of the 1945 Constitution have not been/not formed; (4) recognition of customary law communities should include recognition of indigenous peoples' original beliefs.